Modeling and Integration of Planning, Scheduling, and Equipment Configuration in Semiconductor Manufacturing: Part II. Fab Capability Assessment - Fordyce, Kenneth; Milne, R. John; Wang, Chi-Tai; Zisgen, Horst (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Managing the supply chain of a semiconductor based package goods enterprise—including planning, scheduling, dispatching, and equipment configurations—is a complicated undertaking, particularly in a manner that is responsive to changes throughout the demand supply network. In a companion paper (Part I. Review of Successes and Opportunities), we illustrate the need for industrial engineering teams to serve as agents of change, review prior successes, and highlight issues and opportunities for improvement in this highly integrated decision space. In this Part II paper, we identify modeling challenges and opportunities within a critical component of responsiveness: semiconductor fabrication facility/factory (FAB) capability assessment. This involves estimating the output of the FAB given the current conditions of the FAB (work in process, planned wafer starts, equipment availability and configuration, and other factors). A twin objective of FCA is to determine the actions the FAB should take (how to change the current conditions) to achieve specified output targets.